2016
DOI: 10.1016/j.arabjc.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of CO2 separation from gas mixtures in membrane modules: Effect of chemical absorbent

Abstract: In this study, a mathematical model is proposed for prediction of CO 2 absorption from N 2 /CO 2 mixture by potassium threonate in a hollow-fiber membrane contactor (HFMC). CFD technique using numerical method of finite element was applied to solve the governing equations of model. Effect of different factors on CO 2 absorption was analyzed and for investigation of absorbent type effect, functioning of potassium threonate was compared with diethanolamine (DEA). Axial and radial diffusion can be described with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 74 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…54,55 However, Navier-Stokes equation is more usual and frequently used for calculation of the fluid velocity in the shell for all membrane geometries. The velocity of fluid in the shell side of HFM separator can be determined by Happels free surface model.…”
Section: The Governing Equations In the Shellmentioning
confidence: 99%
“…54,55 However, Navier-Stokes equation is more usual and frequently used for calculation of the fluid velocity in the shell for all membrane geometries. The velocity of fluid in the shell side of HFM separator can be determined by Happels free surface model.…”
Section: The Governing Equations In the Shellmentioning
confidence: 99%
“…3 shows the analysis-of-variance (ANOVA) results for 31 full CCD of the desulfurization efficiency. A polynomial quadratic model for desulfurization in terms of actual parameters, or a so-called modified second-order response surface model, was obtained as follows: þ1:431 10 À6 C SO 2 2 þ 3:839Q 2 þ 0:026T 2 þ 85:531C NH 3 2 À0:002QC SO 2 þ 8:92 10 À5 TC SO 2 À 0:003C SO 2 C NH 3 À 0:374QT À52:972QC NH 3 À 3:37TC NH 3 þ 1:537TQC NH 3 (11) where C SO 2 is the input sulfur dioxide (SO 2 ) concentration, T is the reaction temperature, C NH 3 is the concentration of the ammonia solution, and Q is the flow rate of the polluted air.…”
Section: Experimental Design and Analysis Of Variancementioning
confidence: 99%
“…Nowadays, emission of greenhouse gases is being a major concern worldwide due to their adverse effects on the environment and human life [1][2][3][4][5][6]. Elimination and capture of pollutants emitted into the environment is an essential requirement for human life and for sustainable development as well [7][8][9][10][11][12]. It has been reported that greenhouse gases are produced mainly from burning fossil fuels such as natural gas, petrol, diesel, and crude oil, in which CO 2 an SO 2 are the major greenhouse gases [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane contactors (MCs) have been used for liquid/liquid as well as gas/liquid separation by Rezakazemi et al [36][37][38][39][40] in which the main focus was on model development and simulation of the process. It was reported that hollow-fiber contactors are more effective than other modules owing to their operational properties [41][42][43]. Shirazian et al [44][45][46][47][48][49] studied the use of hollow fibers for CO 2 capture and other gas mixtures by numerical simulation of the contactor system.…”
Section: Introductionmentioning
confidence: 99%